2010
DOI: 10.1111/j.1939-1676.2010.0651.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oral Famotidine and 2 Omeprazole Formulations for the Control of Intragastric pH in Dogs

Abstract: Background: Little is known about the efficacy of commonly used acid suppressants on intragastric pH in dogs. Objective: To compare the effect of oral famotidine, 2 formulations of omeprazole, and placebo on intragastric pH in dogs with a catheter-free, continuous pH monitoring system. Animals: Six healthy adult mixed-breed colony dogs. Methods: Utilizing a randomized, 4-way cross over, open-label study, dogs were administered famotidine PO (1.0-1.3 mg/ kg q12h), omeprazole tablet (1.5-2.6 mg/kg q24h), omepraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
133
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(145 citation statements)
references
References 18 publications
(37 reference statements)
3
133
0
1
Order By: Relevance
“…This result was enough to meet the therapeutic criteria previously described for humans. Previous study to evaluate efficacy of oral omeprazole reported that the MPT with pH ≥4 was 52 ± 17% and 44 ± 18% after treatment with an omeprazole tablet (1.5–2.6 mg/kg q24 hours) and a reformulated omeprazole paste (1.5–2.6 mg/kg q24 hours), respectively 1. The AUC of esomeprazole in people has been reported to be higher than that of omeprazole of the same dose 3.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This result was enough to meet the therapeutic criteria previously described for humans. Previous study to evaluate efficacy of oral omeprazole reported that the MPT with pH ≥4 was 52 ± 17% and 44 ± 18% after treatment with an omeprazole tablet (1.5–2.6 mg/kg q24 hours) and a reformulated omeprazole paste (1.5–2.6 mg/kg q24 hours), respectively 1. The AUC of esomeprazole in people has been reported to be higher than that of omeprazole of the same dose 3.…”
Section: Discussionmentioning
confidence: 99%
“…The duration for which the gastric pH is above 4 has been shown to have a direct relationship to the healing rate in GERD patients, and maintaining the intragastric pH above 4 for at least 16–18 hours is an important therapeutic target for treating these diseases 19, 20. In veterinary medicine, however, no specific standards exist for the duration of drug use or target intragastric pH levels; therefore, MPT for which the pH was ≥3 or ≥4 were considered for dogs as previously reported 1, 11, 21…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations